Interlaboratory comparison on 137Cs activity concentration in fume dust. (November 2015) - Tzika, Faidra; Hult, Mikael; Burda, Oleksiy; Arnold, Dirk; Sibbens, Goedele; Caro Marroyo, Belén; Gómez–Mancebo, Maria Belén; Peyrés, Virginia; Moser, Hannah; Ferreux, Laurent; Šolc, Jaroslav; Dryák, Pavel; et al.
Abstract: A comparison was conducted, between 11 European National Metrology Institutes and EC-JRC, on measurement of 137 Cs activity concentration in fume dust. As test material an activity standard produced from real contaminated fume dust was used. The standard material consisted of 13 cylindrical samples of compressed fume dust. The material contained 137 Cs and 60 Co of reference activity concentrations of (9.72±0.10) Bq/g and (0.450±0.018) Bq/g, respectively, for the reference date of 1 June 2013, determined using the comparison results. The organization and results of the intercomparison, as well as the process of obtaining reliable reference values are presented. Highlights: A European comparison was conducted on measurement of 137 Cs activity in fume dust. Participants used high resolution gamma ray spectrometry. Efficiency calibration included Monte Carlo, numerical and experimental methods. Reference 137 Cs and 60 Co activity concentrations in the fume dust were determined. A new traceable activity standard of fume dust matrix is available to end-users.